PULP Guide: Where to publish articles on the law - Fifth edition - Edited by Shirley Ann Gilmore (Pretoria University Law Press (PULP), 2017)
PULP Guide: Where to publish articles on the law - Fifth edition Edited by Shirley Ann Gilmore 2017 ISBN: 978-1-920538-64-4 Pages: 121 Print version: Available Electronic version: Free PDF available